Effects of silage from maize crops differing in maturity at harvest, grass silage feed value and concentrate feed level on performance of finishing lambs - T.W.J. Keady (Animal, 2013)
The effects of (i) medium and high feed value (MFV and HFV) maize silages and (ii) MFV and HFV grass silages, each in combination with a range of concentrate feed levels, on the performance of finishing lambs were evaluated using 280 Suffolk-X lambs (initial live weight 36.1 kg). The MFV and HFV maize silages represented crops with dry matter (DM) concentrations of 185 and 250 g/kg, respectively, at harvest, and had starch and metabolisable energy (ME) concentrations of 33 and 277 g/kg DM and 9.6 and 11.0 MJ/kg, respectively. HFV and MFV grass silages had DM and ME concentrations of 216 and 294 g/kg and 11.0 and 11.5 MJ/kg DM, respectively. A total of 13 treatments were involved. The four silages were offered ad libitum with daily concentrate supplements of 0.2, 0.5 or 0.8 kg per lamb. A final treatment consisted of concentrate offered ad libitum with 0.5 kg of the HFV grass silage daily. Increasing the feed value of grass silage increased (P < 0.001) forage intake, daily carcass and live weight gains, final live weight and carcass weight. Increasing maize silage feed value tended to increase (P = 0.07) daily carcass gain. Increasing concentrate feed level increased total food and ME intakes, and live weight and carcass gains. There was a significant interaction between silage feed value and the response to concentrate feed level. Relative to the HFV grass silage, the positive linear response to increasing concentrate feed level was greater with lambs offered the MFV grass silage for daily live weight gain (P < 0.001), daily carcass gain (P < 0.01) and final carcass weight (P < 0.01). Relative to the HFV maize silage, there was a greater response to increasing concentrate feed level from lambs offered the MFV maize silage in terms of daily carcass gain (P < 0.05) and daily live weight gain (P = 0.06). Forage type had no significant effect on the response to increased concentrate feed level. Relative to the MFV grass silage supplemented with 0.2 kg concentrate, the potential concentrate-sparing effect of the HFV grass silage, and the MFV and HFV maize silages was 0.41, 0.09 and 0.25 kg daily per lamb, respectively. It is concluded that increasing forage feed value increased forage intake and animal performance, and maize silage can replace MFV grass silage in the diet of finishing lambs as performance was equal to or better (depending on maturity of maize at harvest) than that for MFV grass silage.